Effectively Intervening Epithelial-Mesenchymal Transition of Retinal Pigment Epithelial Cells With a Combination of ROCK and TGF-β Signaling Inhibitors - Chen, Yi (Invest Ophthalmol Vis Sci, 2021)
PURPOSE: Epithelial-mesenchymal transition (EMT) of retinal pigment epithelial (RPE) cells is a key pathological event in proliferative retinal diseases such as proliferative vitreoretinopathy (PVR). This study aimed to explore a new method to reverse EMT in RPE cells to develop an improved therapy for proliferative retinal diseases. METHODS: In vitro, human embryonic stem cell–derived RPE cells were passaged and cultured at low density for an extended period of time to establish an EMT model. At different stages of EMT after treatment with known molecules or combinations of molecules, the morphology was examined, transepithelial electrical resistance (TER) was measured, and expression of RPE- and EMT-related genes were examined with RT-PCR, Western blotting, and immunofluorescence. In vivo, a rat model of EMT in RPE cells was established via subretinal injection of dispase. Retinal function was examined by electroretinography (ERG), and retinal morphology was examined. RESULTS: EMT of RPE cells was effectively induced by prolonged low-density culture. After EMT occurred, only the combination of the Rho-associated coiled-coil containing protein kinase (ROCK) inhibitor Y27632 and the TGF-β receptor inhibitor RepSox (RY treatment) effectively suppressed and reversed the EMT process, even in cells in an intermediate state of EMT. In dispase-treated Sprague-Dawley rats, RY treatment maintained the morphology of RPE cells and the retina and preserved retinal function. CONCLUSIONS: RY treatment might promote mesenchymal-epithelial transition (MET), the inverse process of EMT, to maintain the epithelial-like morphology and function of RPE cells. This combined RY therapy could be a new strategy for treating proliferative retinal diseases, especially those involving EMT of RPE cells.